A rare presentation of herpes simplex virus encephalitis occurring in a pediatric patient on dupilumab for atopic dermatitis. Issue 2 (3rd March 2022) - Rao, Megana; Grove, Daniel; Haggstrom, Anita
Abstract: A 4‐year‐old female with a history of atopic dermatitis developed herpes simplex virus (HSV) encephalitis while being treated with dupilumab and concomitant topical steroids. There was no prior history of HSV infections or immunodeficiency. To our knowledge, this is the first case of HSV encephalitis in a patient receiving dupilumab.